Selectivity Control in the Tandem Aromatization of Bio‐Based Furanics Catalyzed by Solid Acids and Palladium - Genuino, Homer C.; Thiyagarajan, Shanmugam; van der Waal, Jan C.; de Jong, Ed; van Haveren, Jacco; van Es, Daan S.; Weckhuysen, Bert M.; Bruijnincx, Pieter C. A. (ChemSusChem, 2017)
Bio‐based furanics can be aromatized efficiently by sequential Diels–Alder (DA) addition and hydrogenation steps followed by tandem catalytic aromatization. With a combination of zeolite H‐Y and Pd/C, the hydrogenated DA adduct of 2‐methylfuran and maleic anhydride can thus be aromatized in the liquid phase and, to a certain extent, decarboxylated to give high yields of the aromatic products 3‐methylphthalic anhydride and o‐ and m‐toluic acid. Here, it is shown that a variation in the acidity and textural properties of the solid acid as well as bifunctionality offers a handle on selectivity toward aromatic products. The zeolite component was found to dominate selectivity. Indeed, a linear correlation is found between 3‐methylphthalic anhydride yield and the product of (strong acid/total acidity) and mesopore volume of H‐Y, highlighting the need for balanced catalyst acidity and porosity. The efficient coupling of the dehydration and dehydrogenation steps by varying the zeolite‐to‐Pd/C ratio allowed the competitive decarboxylation reaction to be effectively suppressed, which led to an improved 3‐methylphthalic anhydride/total aromatics selectivity ratio of 80 % (89 % total aromatics yield). The incorporation of Pd nanoparticles in close proximity to the acid sites in bifunctional Pd/H‐Y catalysts also afforded a flexible means to control aromatic products selectivity, as further demonstrated in the aromatization of hydrogenated DA adducts from other diene/dienophile combinations. Balancing act: A balance between the acidity and porosity of H‐Y zeolites and efficient coupling with a Pd catalyst is essential for the selective conversion of bio‐based furanics to renewable aromatic chemicals.